A Sensemaking Study of Change Initiative: The Case of A Malaysian Multinational Enterprise (Malaysian Management Journal, 2019)
Empirical evidence has emphasized the need for more research to uncover why does change fail and what can organizations do to improve their success rate. The purpose of this article is to provide an in-depth assessment on the implementation of centre-led change initiative in a novel empirical study in a Malaysian-based multinational enterprise (MNE). This study is based on multiple embedded case studies of four subsidiaries of a Malaysian-based MNE. This study urges centre managers tasked with implementing strategic change initiatives to emphasize the behavioral aspect of those involved in change throughout the entire development stage of the change. Any negative cues from change recipients need to be addressed and attended to as quickly as possible. This study is based on a section within the larger context of the MNE which is being researched. The study contributes to the literature of organizational sensemaking in change by extending the knowledge of new sensemaking forms namely communication intensity and resolution to barriers. This study also contributes to the empirical literature in change by providing an in-depth account of a Malaysian based MNE journey in implementing centre-led change initiatives.